RUMAH SEHAT LANSIA DI KUBU RAYA - Almeina, Andra; Muazir, Syaiful; Affrilyno, Affrilyno (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
Indonesian people are still not used to living separately from elderly family members. Urban areas such as Kubu Raya are included in developing cities where people are dominated by productive age. Elderly people who are not productive and have decreased body functions have different activities. Based on data from public health centers in Kubu Raya, there is no special health service building for the elderly. Special programs for the elderly are only offered in the form of elderly posyandu and nursing homes. Kubu Raya still lacks elderly-friendly public facilities. Especially for natural problems suffered by the elderly both from common (physical) diseases to psychological problems. The design objective is to produce a design of facilities that accommodate the needs of the elderly. The design method is carried out through several stages, namely the idea of theme ideas, problem identification, data collection, analysis, synthesis, and design stages. The result is the concept of a Healthy Elderly Home that provides nature in the space. Facilitating the physical and psychological activity needs of the elderly which is a measure of elderly health. The concept of a therapeutic environment and healthy living modifications in a customized design. Natural elements are believed to have elements that have a positive impact such as improving quality of life, diverting depression, and calming the soul.